Komunikasi Kepemimpinan Kristen: Membangun Hubungan Yang Berakar Pada Integritas dan Kasih Menurut Efesus 4:29 - Yosia Belo; Febrianto Rompis (JURNAL LUXNOS, 2026)
In the current era of disruption and information openness, the greatest challenge in leadership is a crisis of role modeling and relationships, which triggers a deficit of trust due to authoritarian or merely formal communication patterns. This study aims to analyze the Christian leadership communication model rooted in integrity and love based on the exegesis of Ephesians 4:29. Utilizing a qualitative approach through literature research method, this study examines the text of Ephesians 4:29 as primary data, supported by theological literature and organizational communication theories as secondary data. The results of the exegetical analysis reveal a sharp theological contrast between the prohibition of uttering unwholesome words (sapros) that damage relationships, and the command to speak what is good for building up (oikodomē) according to needs, thereby imparting grace (charis) to the hearers. This study concludes that the implementation of this communication ethics relies on integrity (the absolute alignment between inner truth and verbal articulation) and love (oriented toward the restoration and growth of members). On a practical level, this model is capable of transforming the organizational climate into a healthy environment through educational evaluation spaces, reconciliatory conflict management, and the creation of psychological safety.